Experimental Study of Artificial Coarse Aggregate Materials Made from Fly Ash - Rajiman Rajiman; Ronny Hasudungan Purba; Inggit Anugriyya Netriza (International Journal of Mechanical, Electrical and Civil Engineering, 2026)
In general, infrastructure development requires materials from nature and one of them is natural coarse aggregate of crushed stone. The rapid development of infrastructure in Indonesia has resulted in the depletion of the natural coarse aggregate. Therefore, other efforts are needed in terms of using coarse aggregate as a construction material. So in this study the aim is to make artificial coarse aggregate made from fly ash. The results showed that this artificial coarse aggregate met the requirements of the General Specifications of Bina Marga 2010 rev 3 as a construction material, namely for an abrasion value of 40% and water absorption of 3%. In this study, 5 types of comparisons were carried out, namely, 70:30%, 60:40%, 50:50%, 40:60%, 30:70 and for the type of composition comparison 70:30% (70% fly ash:30% cement). ) the abrasion value is still below 40%, and the amount of water absorption is below 3% so that this artificial coarse aggregate still meets the standard specifications of General Highways 2010 rev 3. Based on the price comparison that has been made between artificial coarse aggregate and natural coarse aggregate of crushed stone , shows a price disparity of Rp. 35,779 - Rp. 58,779. Thus, this artificial coarse aggregate is one solution that can be developed to reduce the environmental impact due to the presence of fly ash which is quite abundant in Indonesia.